(untitled) (Research, Society and Development, 2022)
The study and anatomical mastery of the human body are essential for professional practice. Among the subdivisions of human anatomy, neuroanatomy has a potential degree of complexity as it encompasses knowledge involving the central and peripheral nervous system, especially the brachial plexus, requiring the ability to associate and memorize. The study aimed to create and develop an active strategy for teaching the anatomy of the brachial plexus, demonstrating its structure and formation to associate with its function, in addition to encouraging the adoption of a central position in teaching and learning. For the construction of the piece, an MDF board, five boxes of modeling clay, adhesive paper, printer, hot glue, scissors and ruler were used. The design was made on the plate and the brachial plexus was molded with modeling clay according to the colors assigned to each segment. The activity was a proposal used to guarantee the insertion of students in the teaching-learning process, seeking to modify the traditional structure of the current teaching model that is configured centered on learning through memorization and transfer of information. Strategies were developed using different colors that integrate dynamically, allowing and stimulating interaction with the content, adding to the construction of knowledge and still becoming a useful alternative to supply the scarcity of synthetic and cadaveric anatomical models. The active methodology proved to be an efficient didactic approach in promoting learning, as an effective way of complementing the teaching-learning process of Human Anatomy, making the student protagonist in the construction of knowledge.